Isolation and characterization of bacteria from door handles at UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah / Muhammad Anas Mohamad Arbaain - Mohamad Arbaain, Muhammad Anas (2018)
Bacteria are microscopic organisms that occupied the nature widely from the living organisms until the non-living organisms. Bacteria are so small that cannot be seen by our naked eyes and exist everywhere. The bacteria can be transmitted from one place to another by medium or fomite. Example of fomite is the door handles. The door handles are most widely used by the humans and become major place of bacteria transmission. A study was conducted by isolation and characterization of bacteria from the door handles at UITM Cawangan Negeri Sembilan Kampus Kuala Pilah, Negeri Sembilan, Malaysia. The samples were collected by swabbing the sterile cotton swab through the object and inoculated at the nutrient agar and MacConkey agar. The bacteria samples were further characterized by gram staining and series of biochemical tests. Twelve isolated bacterial colonies were obtained in this study. Eight colonies were identified while other four were not identified, based on their morphological characteristics of growth on the agar medium and ten biochemical tests carried out in this study. The bacterial isolates successfully identified were Staphylococcus spp., Bacillus spp., and Lactobacillus spp.